Ecosystems in action - Stonebarger, Bill; Hawkhill Associates Inc. (Wisconsin : Hawkhill Associates Inc., 2002)
This series is designed to help teachers of ecology and environmental studies by providing vivid examples of three different ecosystems for each volume. Each program illustrates general principles of ecology and also stresses what is special about a particular ecosystem
Title from title screen
vol. 1. : A tropical rain forest (24 min.) - Deserts (29 min.) - The Galapagos Islands (21 min.). - vol. 2. : The great lakes ecosystem (21 min.) - A new England pond (23 min.) - The web of life (22 min.)
Music and sound, Eric Nelson, Roy Gustarson, Michael Stonebarger
Keywords: Biotic communities; Desert ecology; Rain forest ecology; Pond ecology; Freshwater ecology -- Great Lakes (North America).; Galapagos Islands